Response of Sugarcane Varieties to Gluconacetobacter diazotrophicus and Phosphate Solubilizing Bacteria-Induced Nitrogen and Phosphorus - S.V. Nalawade; D. V. Indi; S. U. Deshmukh; R. L. Bhilare; K. D. Bhoite; S. K. Ghodake (Current Research Progress in Agricultural Sciences Vol. 1, 2024)
Aims: The present study highlights the effect of Gluconacetobacter diazotrophicus and PSB inoculation on two sugarcane varieties in different problematic soils and the possibility of saving chemical fertilizer nitrogen and phosphorus. Methods: A pot culture experiment was conducted under natural conditions in a 6 x 2 x 2 factorial completely randomized design (FCRD) with two replications during the Suru season (January planting) of 2012-13 at Central Sugarcane Research Station, Padegaon, Tal. Phaltan, Dist. Satara (Maharashtra state, India). The single eye bud sets were inoculated with G. diazotrophicus 10 kg + PSB 1.25 kg in 100 lit water/ha for 30 min before planting and the pots planted with such treated sets received 50% recommended N (125 kg/ha) and 75% recommended P2O5 (86.25 kg/ha). The corresponding control pots planted with the untreated bud sets received 100% recommended N (250 kg/ha) and P2O5 (115 kg/ha). Results: The results indicated that the treatment of sugarcane bud sets with G. diazotrophicus 10 kg + PSB 1.25 kg in 100 lit water/ha for 30 min. coupled with 50% recommended N and 75% recommended P significantly improved the growth, yield and quality. The overall performance of the varieties was best in the normal soil (S-6) followed by S-4 (Sodic) and S-1 (Sodic). The inoculation of sugarcane sets showed the best results in normal soil (S-6) closely followed by S-4 (Sodic) and S-1 (Sodic) indicating better performance of inoculation in these problematic soils. The higher population and activity of G. diazotrophicus and PSB was observed at 50% recommended N and 75% recommended P in both the varieties. Conclusion: The pre-planting bud set treatment in sugarcane with G. diazotrophicus + PSB coupled with 50% recommended N and 75% recommended P significantly improved the growth, yield and quality of cane juice. Bud set treatment showed the best results in normal soil closely followed by sodic soils indicating better performance of inoculants in these problematic soils. The increase in soil nitrogen reserve under sugarcane crop by 50 % of the initial value due to the nitrogen fixation by root-associated diazotrophs helping sustained production of sugarcane.